2018
DOI: 10.3892/mco.2018.1753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the timing of discontinuation of last‑line chemotherapy on patient prognosis in advanced and recurrent gastric cancer

Abstract: The present study aimed to determine the effect of the timing of treatment discontinuation on the prognosis of patients with advanced and recurrent gastric cancer chemotherapy. Between July 2014 and March 2017, 127 patients who underwent chemotherapy for advanced and recurrent gastric cancer at Ogaki Municipal Hospital (Ogaki, Japan) were examined. To determine factors associated with survival, multivariate analysis using the Cox proportional hazards model, and hazard ratios and their 95% confidence intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, in patients with advanced hepatocellular carcinoma in Japan, significant correlation between total duration of administration of all tyrosine kinase inhibitors and OS was observed [22]. For AGC patients in Japan, the reported survival time after discontinuing therapies is relatively short compared with the overall therapy duration [23,24], suggesting an association between overall therapy duration and OS, although further verification is required. Transition to subsequent therapy has been reported to be associated with better survival [25][26][27], and a meta-analysis concluded that AGC patients treated with 3L therapy had significantly longer OS compared with patients treated with best supportive care only [28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients with advanced hepatocellular carcinoma in Japan, significant correlation between total duration of administration of all tyrosine kinase inhibitors and OS was observed [22]. For AGC patients in Japan, the reported survival time after discontinuing therapies is relatively short compared with the overall therapy duration [23,24], suggesting an association between overall therapy duration and OS, although further verification is required. Transition to subsequent therapy has been reported to be associated with better survival [25][26][27], and a meta-analysis concluded that AGC patients treated with 3L therapy had significantly longer OS compared with patients treated with best supportive care only [28].…”
Section: Discussionmentioning
confidence: 99%